2012
DOI: 10.1902/jop.2012.110658
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supra‐ and Subphysiologic Testosterone Levels on Ligature‐Induced Bone Loss in Rats — A Radiographic and Histologic Pilot Study

Abstract: Both sub- and supraphysiologic testosterone levels may influence bone metabolism, but only subphysiologic levels significantly increase ligature-induced bone loss. Moreover, testosterone has a regulatory effect on the gingival area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 37 publications
0
32
1
1
Order By: Relevance
“…This group of people generally use the compounds at concentrations of 10–100 times higher than normal [37]. We have recently shown that serum concentration of testosterone was approximately 7 nM in rats; a 10-fold reduction in these levels can be obtained following orchiectomy as a model of late onset hypogonadism in a rat model [34]. In parallel, the findings from our previous study and the current work showed that rats can be used for low or high levels of testosterone studies, with the advantage of enabling evaluation of the hormonal imbalances in vivo and ex vivo analyses [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This group of people generally use the compounds at concentrations of 10–100 times higher than normal [37]. We have recently shown that serum concentration of testosterone was approximately 7 nM in rats; a 10-fold reduction in these levels can be obtained following orchiectomy as a model of late onset hypogonadism in a rat model [34]. In parallel, the findings from our previous study and the current work showed that rats can be used for low or high levels of testosterone studies, with the advantage of enabling evaluation of the hormonal imbalances in vivo and ex vivo analyses [34].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that serum concentration of testosterone was approximately 7 nM in rats; a 10-fold reduction in these levels can be obtained following orchiectomy as a model of late onset hypogonadism in a rat model [34]. In parallel, the findings from our previous study and the current work showed that rats can be used for low or high levels of testosterone studies, with the advantage of enabling evaluation of the hormonal imbalances in vivo and ex vivo analyses [34]. Our results also reveal that testosterone modulates periodontal bone loss in an inflammatory environment without resulting in any significant change in healthy animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many in vitro studies assess the role of androgens on different periodontal soft tissue cells: in gingival connective tissue testosterone inhibits prostaglandin formation [26], in inflamed gingiva androgens increase 5-alpha-reductase activity [27]; and in fibroblasts, increasing concentrations of androgens inhibit IL-6 production [28, 29] and increase cell proliferation [30]. Previous studies have demonstrated that low and high testosterone levels in rats increase both gingival and connective tissue areas [13], increase periodontal bone loss; and impact the release of RANKL and osteoprotegerin by murine osteoblasts [14]. …”
Section: Discussionmentioning
confidence: 99%
“…This overproduction leads to tissue breakdown and the consequent resorption of the alveolar process, a bone structure consisting of outer cortical plates of compact bone, a central spongiosa (trabecular bone), and bone lining the alveolus (alveolar bone) [21]. Our previous studies suggest that both low and high testosterone levels regulate experimental bone loss in rats [13, 14]. This study tests the hypothesis that testosterone suppression increases inflammation-induced bone loss through the reduction of androgen receptor activation.…”
Section: Introductionmentioning
confidence: 99%